Role Government Area In Reduction Poverty In Regency Siden Raping - Zainuddin, Irvaniya; Ahmad, Jamaluddin; Ramadhan, Muhammad Rohady (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Poverty has long been a major challenge for developing countries including Indonesia. The decline in poverty rates from year to year to year in Indonesia shows a continuing decline. A similar downward trend also occurred in Sidenreng Rappang Regency known as the City of Rice, although the graph has fluctuated slightly. This study examines how the role of government regions in eradicating poverty and the obstacles encountered. The authority of local governments has increased since the birth of autonomy area as effort decentralization power. Decentralization is Wrong One actualization New Public Management . Based on the transformation of public administration, researchers use the theory of the development of the public administration paradigm from Old Public Administration (OPA), became New Public Management (NPM), until the birth of New Public Service (NPS). Denhardt and Denhardt (2013) mentioned 3 dimensions of the government's role, namely rowing, steering , and serving . Using a descriptive research method qualitative, The results found were that the role of local government in the rowing dimension resulted in Regional Regulation No. 3 of 2019. The role of steering realized with the involvement of third parties such as Baznas in poverty alleviation programs. Then the role of serving is depicted through direct assistance programs such as plant seed assistance, house renovation, basic necessities, cheap markets, and entrepreneurial skills training which is expected to be able to improve the quality of life of the poor. The obstacles found were the lack of coordination and cross-sector communication of OPDs in implementing poverty alleviation programs, individual characteristics of unproductive poor communities and low quality of human resources, also invalid data on poor people. As an anticipation of communication constraints between OPDs and validity of the data, the government developed a system called SI-PEKA for monitoring and verifying data on poor people based on database by name by address .